Toxicity of Ochratoxin to Early Life Stages of Zebrafish (Danio rerio) - Linda Tschirren; Seraina Siebenmann; Constanze Pietsch (Toxins, 2018)
Ochratoxin A (OTA) is a known contaminant in fish feed but its effect on fish health remains rather unknown. A study was conducted to investigate the effects of different concentrations of ochratoxin on early life stages of zebrafish (Danio rerio). The tests with ochratoxin A showed a correlation between the exposure to mycotoxin and the amount of damage. The mortality rate and the incidents of embryonal damage was increased by increasing ochratoxin concentrations. The calculations resulted in a lethal concentration for 50% of the embryos (LC50) of 0.29 mg/L and a concentration at which 50% of the animals showed impairment (EC50) of 0.36 mg/L after 96 h of exposure. During the test, reduced heart rates were also observed revealing a clear dose-response relationship. The EC50 determination for this endpoint was 1.26 mg/L after 72 h of exposure. The measurement of oxidative stress was proven to be the most sensitive system to indicate OTA effects on the zebrafish embryos with an EC50 value of 0.067 mg/L after 72 h of exposure. The test validity was given because the control test with 3,4-Dichloroaniline (3,4-D) showed a LC50 value of 2.88 mg after 96 h of exposure which is comparable to the available reference values. According to the current knowledge, these experimental doses did not exceed the environmental concentrations of this ochratoxin A. However, this study raises concerns about the effects of ochratoxin on fish.